Tourism Village Development Strategy Through The Role Of Tourism Awareness Community Empowerment Groups (Pokdarwis) (Case Study Of The Sanan Tempe Chips Industry Center Association In Purwantoro Village, Blimbing District, Malang City) - Heribertus; Cakti Indra Gunawan; Moh. Askiyanto (International Research & Development for Human Beings (IRDH), 2025)
This study was conducted with the aim of finding out what strategies are carried out by the association in developing the Tempe Sanan tourist village in Purwantoro Village, Blimbing District, Malang City , to find out how the role of the tourism-aware community empowerment group is in developing the Tempe Sanan tourist village in Purwantoro Village, Blimbing District, Malang City , to find out how Public Awareness is towards developing the Tempe Sanan tourist village in Purwantoro Village, Blimbing District, Malang City. The research design in this study uses a qualitative approach method. Research with this qualitative method is research that intends to describe and understand the phenomenon of what is experienced by the research subject, for example regarding the strategy for developing a tourist village through the role of the tourism-aware community empowerment group (pokdarwis). development strategy of Tempe Sanan Tourism Village is Pokdarwis tourism education, which includes teaching about tempe production, preparation, and processing. Pokdarwis Tempe Sanan Tourism Village, must collaborate with the city government and the community to understand the existing market and take advantage of all potential opportunities. However, opening up the knowledge of village communities by socializing about safety in the tourist environment, maintaining cleanliness, preserving tourism assets, and being a friendly host for visitors